Needs-Based Assessment of Twice-Exceptional Gifted Students: The S&W-Heuristic - Burger-Veltmeijer, Agnes; Minnaert, Alexander (Advances in Social Sciences Research Journal, 2023)
Misdiagnoses and missed diagnoses of gifted students with co-occurring learning-, developmental and behavioural disorders are often mentioned in literature and practice. Consequently, these Twice-Exceptional (2E) students often fall between two stools regarding appropriate psycho-educational interventions. This article offers a research and practice informed assessment procedure, namely the Strengths and Weaknesses Heuristic (S&W-Heuristic), that can help to tackle such problems in case giftedness or any 2E is suspected. This S&W-Heuristic was developed via the method of design research. Initially the S&W-Heuristic was developed to assess students with (suspicion of) the co-occurrence of intellectual giftedness (IG) and autism in a needs-based way, though, subsequently to assess (potential) 2E-students in general. The systematicity of the S&W-Heuristic may help psychologists and special remedial educationalists to reveal hitherto camouflaged strengths or weaknesses in underachieving smart students and to understand their ambivalent psycho-educational needs. Being the product of design research, this article also offers a prelude to new theoretical perspectives regarding the concepts IG and 2E. By shifting from a ‘classification-based’ to a dynamic ‘dimensional-based’ definition of 2E, camouflaged talent will be recognised more effectively and will get more opportunity to flourish. Accordingly, it is proposed to consider IG and 2E as constructs on a continuum.